Addendum to Zootaxa 4683 (4): Popillia biguttata (Wiedemann in Wiedemann & Germar, 1821) (Coleoptera: Scarabaeidae: Rutelinae) established on New Guinea? With an illustrated key to Sundaland Popillia Dejean species - Telnov, Dmitry; Zorn, Carsten (Zootaxa, 2020)
In our recent publication (Telnov & Zorn 2019) we overlooked and did not include Popillia migliaccioi Sabatinelli, 1996, described from “Java”, in our checklist and key of Sundaland Popillia species. However, the examination of the holotype of this species deposited in the Muséum d’Histoire Naturelle, Geneva, Switzerland (Figs. 1–8) revealed that Popillia migliaccioi is in fact an Afrotropical species, which was already described under the name Popillia maynei Ohaus, 1914. It is obvious that the specimen studied and described by Sabatinelli (1996) is mislabelled and is not from Java (Fig. 8). Unfortunately, the type material of P. maynei, which is housed in the Museum für Naturkunde, Berlin, Germany, is on loan indefinitely and was not available for our study (Bernd Jäger, personal communication). However, the original description of P. maynei and the aedeagus as originally figured by Ohaus (1914) (Fig. 9) match habitus and aedeagus of the P. migliaccioi holotype perfectly (Figs. 4–6). Habitus photographs of an additional comparative specimen from Togo (Kloto, III.2015, Don P. Léonard, deposited in the Royal Belgian Institute of Natural Sciences, Brussels, Belgium) are provided for comparison in figs. 10 and 11.